2019
DOI: 10.1155/2019/7824684
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin Gallate Protects HBMVECs from Ischemia/Reperfusion Injury through Ameliorating Apoptosis and Autophagy and Promoting Neovascularization

Abstract: Green tea is one of the most beverages with antioxidants and nutrients. As one of the major components of green tea, (-)-epicatechin gallate (ECG) was evaluated for its antioxidative properties in the present study. Cell proliferation assay, tube formation, cell migration, apoptosis, and autophagy were performed in human brain microvascular endothelial cells (HBMVECs) after oxygen-glucose deprivation/reoxygenation (OGD/R) to investigate potential anti-ischemia/reperfusion injury properties of ECG in vitro. Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…The protective effect of ECG on cells subjected to OGD was consistent with EGCG [97]. Moreover, ECG protected human BMVECs against ischemic insult by promoting neovascularization and modulating apoptosis and autophagy [111].…”
Section: Flavan-3-olssupporting
confidence: 66%
“…The protective effect of ECG on cells subjected to OGD was consistent with EGCG [97]. Moreover, ECG protected human BMVECs against ischemic insult by promoting neovascularization and modulating apoptosis and autophagy [111].…”
Section: Flavan-3-olssupporting
confidence: 66%
“…48 Epicatechin gallate can protect HBMVECs from IR injury by ameliorating apoptosis and autophagy, but Alliin alleviates myocardial IR injury by promoting autophagy. 49,50 Initial autophagy is an important defence mechanism to remove damaged cell structures and aging organelles from degraded cells. However, excessive autophagy and apoptosis in the latter stages cause hepatocyte death and aggravate damage of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Current research had shown that these substances have significant immune and anti-inflammatory effects [ 38 ], as well as their regulation of endocrine function. Recent research shows that the tea catechin epigallocatechin (gallate) can inhibit NF-κB-mediated transcriptional activation [ 39 ], another recent shows epicatechin gallate can protect HBMVECs from ischemia–reperfusion injury by promoting neurovascular regeneration [ 40 ]. The dietary intake of catechin and epicatechin can reduce vascular damage in high homocysteine intake mice, and reduce endothelial dysfunction and endothelial inflammation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%